2015
DOI: 10.1016/j.envint.2014.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure changes in association with black carbon exposure in a panel of healthy adults are independent of retinal microcirculation

Abstract: Exposure to ambient particulate matter and elevated blood pressure are risk factors for cardiovascular morbidity and mortality. Microvascular changes might be an important pathway in explaining the association between air pollution and blood pressure. The objective of the study was to evaluate the role of the retinal microcirculation in the association between black carbon (BC) exposure and blood pressure. We estimated subchronic BC exposure based on 1-week personal measurements (μ-Aethalometer, AethLabs) in 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 42 publications
1
33
0
Order By: Relevance
“…60-62 A number of studies (although not all 63 ) have produced reports of associations between elevated blood pressure and long-term exposure to residential air pollution or traffic, [64][65][66] with stronger effects noted in older individuals 67 and people with CVD. 68 The prevalence of hypertension-a leading risk factor for CVD-was 9% higher in people living ≤100 m from a major road than in those living ≥1,000 m from such a road.…”
Section: Blood Pressure and Vascular Functionmentioning
confidence: 97%
“…60-62 A number of studies (although not all 63 ) have produced reports of associations between elevated blood pressure and long-term exposure to residential air pollution or traffic, [64][65][66] with stronger effects noted in older individuals 67 and people with CVD. 68 The prevalence of hypertension-a leading risk factor for CVD-was 9% higher in people living ≤100 m from a major road than in those living ≥1,000 m from such a road.…”
Section: Blood Pressure and Vascular Functionmentioning
confidence: 97%
“…Deposited BC reduces the Earth's surface albedo and accelerates snow and ice melting processes (IPCC 2013;Flanner and Zender 2006). The adverse effects of BC aerosols on human health have also been investigated (Croft et al 2017;Li et al 2016;Louwies et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Increase of peripheral vascular resistance is one of the major pathological changes of hypertension, which relates to the changes of blood vessel function and vasoconstrictor hyperresponsiveness . To date, current researches reported that exposure to PM 2.5 induces cardiovascular hyperreactivity, alters the microvascular and macrovascular reactivity, increase vasoconstriction and changes the peripheral resistance of the blood vessels . Mesenteric artery has been regarded as a representative of a peripheral resistance vessel .…”
Section: Discussionmentioning
confidence: 99%
“…18 To date, current researches reported that exposure to PM 2.5 induces cardiovascular hyperreactivity, 19 alters the microvascular and macrovascular reactivity, increase vasoconstriction 20 and changes the peripheral resistance of the blood vessels. 21,22 Mesenteric artery has been regarded as a representative of a peripheral resistance vessel. 23,24 Nonetheless, the mechanism of PM 2.5 -induced mesenteric arteries vascular hyperreactivity has not been satisfactorily elucidated.…”
Section: Pm 25 Increased Mrna Expressions Of Inflammatory Mediatorsmentioning
confidence: 99%